2017
DOI: 10.1016/j.jfranklin.2016.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Channel equalization and beamforming for quaternion-valued wireless communication systems

Abstract: Quaternion-valued wireless communication systems have been studied in the past. Although progress has been made in this promising area, a crucial missing link is lack of effective and efficient quaternion-valued signal processing algorithms for channel equalization and beamforming. With most recent developments in quaternion-valued signal processing, in this work, we fill the gap to solve the problem by studying two quaternion-valued adaptive algorithms: one is the reference signal based quaternion-valued leas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…From (2), it can be learned that g m , m ∈ [1,3], is a column vector with two elements and Ω is a matrix with two columns. Then (18) and (19) can be changed to…”
Section: A Extension Of the Traditional Music Estimator To 4-dmentioning
confidence: 99%
See 1 more Smart Citation
“…From (2), it can be learned that g m , m ∈ [1,3], is a column vector with two elements and Ω is a matrix with two columns. Then (18) and (19) can be changed to…”
Section: A Extension Of the Traditional Music Estimator To 4-dmentioning
confidence: 99%
“…For a DST signal, the two sub-signals have the same DOA but different polarizations. One DST example is to use two orthogonal linearly polarized signals with amplitude or phase modulation [18]- [20]. However, there has rarely been any research reported on estimating the DOAs of DST signals.…”
Section: Introductionmentioning
confidence: 99%
“…For the Q-Capon beamformer, the weight vector is calculated by For the proposed full Q-Capon beamformer, in addition to calculating R −1 , 32N 2 real multiplications are needed to calculate R −1 C and 32M 2 + 32M + 96 real multiplications for (C H R −1 C 0 ) −1 f. In total, the number of real-valued multiplications is 16 3 M 3 + 64M 2 + 272 3 M + 96, which is roughly half that of the Q-Capon beamformer.…”
Section: Complexity Analysismentioning
confidence: 99%
“…Since the output of a quaternion-valued beamformer is also quaternion-valued, only two components of the quaternion are used to recover the SOI, which leads to redundancy in both calculation and data storage. However, with the development of quaternion-valued communications [14][15][16], it is very likely that in the future we will have quaternion-valued signals as the SOI, where two traditional complex-valued signals with different polarisations arrive at the antenna array with the same DOA. In such a case, a full quaternion-valued array model is needed to compactly represent the four-component desired signal and also make sure the four components of the quaternion-valued output of the beamformer are fully utilised.…”
Section: Introductionmentioning
confidence: 99%
“…From [9], [10], based on the instantaneous gradient result, the optimum solution w opt should satisfy…”
Section: B the Wiener Solutionmentioning
confidence: 99%